Molecular, Morphological and Production Performance Analysis of Introduced Black Tilapia Strains Oreochromis sp. - Yanti, Dwi Hany; Soelistyowati, Dinar Tri; Carman, Odang; Hardiantho, Dian; Nasrullah, Hasan; Alimuddin, Alimuddin (Universitas Gadjah Mada, 2025)
Evaluating the introduced black tilapia strains from molecular to production performance is essential in aquaculture to ensure genetic purity, reproductive efficiency and sustainable production improvement. However, uncontrolled hybridization and limited molecular evaluation of introduced strains have often led to inconsistent performance in hatcheries and grow-out systems. This study aimed to identify and characterize introduced black tilapia strains from Thailand (MAG NIN, BIG NIN and GIFT) compared to locally developed SAKTI strain from Indonesia based on molecular, morphological and production performance aspects. Molecular characterization was performed using cytochrome oxidase subunit I (COI) gene sequences from three fish per strain. Morphological aspects were assessed based on body dimensions and proportions from ten fish per strain. Production performance focused on reproductive and growth parameters. Reproductive parameters including fecundity, egg size, hatching rate and larval survival rate, while growth performance parameters comprised specific growth rate, aquaculture productivity, feed conversion ratio, sex ratio and survival rate. Results revealed that all introduced strains shared the same species as the SAKTI strain, identified as Oreochromis niloticus. Morphologically, BIG NIN exhibited a significantly longer body shape compared to other strains (p < 0.05). BIG NIN also demonstrated superior production performance (p < 0.05). These findings highlight the importance of integrating molecular and performance-based evaluations to support selective breeding and strain improvement programs for enhancing tilapia productivity.